A new interpolative homogenization model for evaluation of the effective elasto-plastic responses of two-phase composites. (15th February 2019) - Tian, Wenlong; Qi, Lehua; Chao, Xujiang; Liang, Junhao; Fu, M.W.
Abstract: To accurately predict the effective elasto-plastic responses of two-phase composites, an interpolative M-T/D-I mean-field homogenization model with the tangent formulation is proposed, and the numerical implementation algorithm of the proposed M-T/D-I model with the tangent formulation is presented. The comparisons between the effective elastic properties and elasto-plastic responses of two-phase composites predicted by the M-T/D-I model with the tangent formulation and the RVE based FE homogenization method show that the M-T/D-I model with the tangent formulations can accurately evaluate the effective mechanical properties of two-phase composites. The simulation results demonstrate that the elastic properties of two-phase composites predicted by the M-T/D-I model are more accurate than those predicted by the D-I and M-T models, and the effective elasto-plastic responses of two-phase composites predicted by the M-T/D-I model vary in the range of those predicted by the D-I and M-T models. It is revealed that the M-T/D-I model with the tangent formulation allows to simulate the tensile/compression and biaxial tensile/shear elasto-plastic responses of two-phase composites. Lastly, the effects of the inclusion volume fraction and elastic properties on the effective elasto-plastic responses of two-phase composites are discussed for showing the capability of the proposed interpolative M-T/D-I model with the tangent formulation.